Respiratory Failure due to Transfusion Related Acute Lung Injury (TRALI) and Atelectasis and Acute Kidney Injury Post Cardiac Surgery: A Case Report - wullur, caroline; Sitanggang, Ruli Herman (Perdatin Pusat, 2015)
Postoperative pulmonary complications and acute kidney injuries are the most frequent and significant contributor to morbidity, mortality and costs associated with hospitalization. Despite the prevalance of these complications in cardiac surgery patients, recognition, diagnosis and management of this problem vary widely. Many factors may contribute to the pathogenesis of lung complications include atelectasis, Transfusion Related Acute Lung Injury (TRALI) and Acute Respiratory Distress Syndrome (ARDS). While haemodynamic, inflammatory and nephrotic factors are involved and overlap each other in leading to kidney injury. A 54-year-old patient with history of hypertension and diabetes melitus underwent coronary artery bypass graft. On postoperative day 1, he had worsening respiratory and renal function with suspected atelectasis and TRALI. Alveolar lung recruitment maneuvers as well as Sustained Low-Efficiency Dialysis (SLED) were conducted. He was transferred to regular ward on postoperative day seven and discharged uneventfully two days later. Early recognition and management including alveolar recruitment maneuvers and dialysis have an important role in the prevention and treatment of these complications.